Pengembangan Aplikasi Klinik Kecantikan sebagai Pengelola Transaksi berbasis Android menggunakan Metode Prototype (Studi Kasus :Klinik Kecantikan CV Nana Beautyskin) - Agung Dwi Saputra; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Proper marketing and information management can help business owners manage their business, such as planning activities and business financial analysis in order to maximize the use of business capital properly. The problems that occur at CV.Nana Beautyskin are problems in managing transaction data due to the large number of transactions that occur so that carelessness often occurs in the form of transactions that are not recorded or missed, because until now the recording is only based on manual book records that are carried out every day, so that feels less efficient when the transaction is busy. Based on these problems, the authors provide a solution in the form of developing a beauty clinic application as an Android-based transaction manager, in order to be able to record transactions directly every time there is a transaction activity. Application development uses the prototype development method. The application development process has several stages, namely requirements analysis, system design, prototype development, evaluation, implementation and system testing. Based on the iteration that is carried out 2 times, a total of 32 needs with 4 types of actors are obtained. Implementation using the Java programming language on android applications. Tests carried out in the form of unit testing based on 3 test samples, integration produced valid results, validation testing obtained 100% valid from 68 test cases, non-functional in the form of usability testing using the SUS method (System Usability Scale) got a value of 78 obtained from 17 respondents and compatibility get the results that the application can run well on the Android operating system starting from Lollipop, Marshmallow, Nougat, Oreo, Pie and Q.